Fostering the valorization of organic wastes into carboxylates by a computer-aided design tool. (1st April 2022) - Saavedra del Oso, Mateo; Regueira, Alberte; Hospido, Almudena; Mauricio-Iglesias, Miguel
Graphical abstract: Highlights: A computer-based tool to assess the potential of wastes for conversion into VFA. The tool includes a library with 8 fully characterised wastes. It reproduces the dependency of VFA stoichiometry with fermentation pH and substrate. Two case-studies of waste screening and fermentation design are included. Tool applications reported in the (waste-to-chemical) carboxylate platform. Abstract: The carboxylate platform has the potential to constitute an outstanding opportunity for converting organic wastes into chemicals and other value-added products within a circular economy framework. However, its development is still hampered by technological and financial constraints due to difficulties at forecasting the carboxylates yields by different wastes. This work provides a framework that can be the key to foster circular economy and bridge the development risks, allowing early-stage evaluation of process performance. This framework, which is implemented as a computer-aided design tool, is comprised by: (i) a library of substrates including their characterization and appropriate kinetic parameter selection, (ii) an integral kinetic and stoichiometric model which solves both identified gaps regarding the disintegration mechanisms and the acidogenic stoichiometry variability in the anaerobic mono and cofermentation of complex organic wastes, and (iii) a set of indicators to interpret simulation results and assist the decision making; and presents a showcase of applications supported by two case studies. These case studies show that the optimal conditions to steer VFA spectrum towards odd-chain VFA in MCF of regrind pasta are neutral pH (6.5–7) and a relatively low HRT (3–4 days), while cofermentation of tuna canning wastewater and regrind pasta follows interactive mechanisms that cannot be captured by a "naïve approach", i.e. by adding up the individual contributions. Finally, it is discussed how value chain actors with different interests can benefit from the proposed tool: identifying technical, economic, and environmental bottlenecks, and proposing innovative solutions prior to costly lab research and piloting.